Psychological and cultural adaptation of foreign students to the new educational environment - Kostyushina, Yuliya I.; Yuliya A. Tikhonova, Natalia N. Stroiteleva, Alisa V. Lobuteva, (Opción, 2020)
The study aims to investigate issues of psychological and cultural adaptation of foreign students to the new educational environment via comparative quantitative research methods. This work demonstrates that in order to diminish the intercultural gap it is necessary to change the perception of the cultural gap. The results of the study have incorporated the totality and interconnection of all semantic concepts of the psychological adaptation of a foreign student.